First record of spotted linsang Prionodon pardicolor (Hodgson, 1841) (Mammalia: Carnivora: Prionodontidae) with photographic evidence in Khotang and Bhojpur, Eastern Nepal - Baral, Badri; Basnet, Dipak Raj; Rai, Jeevan (Nepalese Journal of Zoology, 2025)
Information on a globally ‘Least Concern’ and nationally ‘Endangered’ spotted linsang Prionodon pardicolor via camera trap image offers hope to address Wallacean shortfall outside the Protected Area in its range. The present paper reports the first verified record of its occurrence outside the Protected Areas in Khotang and Bhojpur districts, east Nepal.